Public Deliberation and Civic Engagement in Public Health Politics: Everyday Political Talk about Public Health Issues on Chinese BBS forums - Sun, Yu; Graham, Todd; Broersma, Marcel (AoIR Selected Papers of Internet Research, 2017)
This study empirically explores how ordinary Chinese citizens engage in public health politics through everyday online political talk about public health topics and whether it serves as a way to strengthen the public’s position in health governance. Moving beyond the formally political spaces such as official institutions and social organisations, this research investigates ordinary online political conversations in the potential space of everyday life. Specifically, it attempts to address this question by examining how the political emerges in ordinary online conversations about public health topics outside of formal political sphere and how public deliberation and other modes of social-civic practices arise in the course of such talk. For this purpose, a comparative content analysis of everyday political talk across three different Chinese online forums was conducted to better understand how ordinary Chinese citizens talk about public health issues in different contexts. It was guided by a two-level coding scheme which included: a normative assessment of the deliberativeness of political talk and an examination of other non-deliberative civic behaviours. This coding scheme was created to answer: 1) what is the deliberative quality of the everyday political talk about public health issues? 2) what other modes of civic engagement such talk triggers, enhancing ordinary citizens’ civic agency and amplifying their civic life? The research concludes with the argument that everyday political talk on the forums was not necessarily ‘deliberative’ as Habermas envisioned, but it engaged more fully with disorganised people of multiple social and civic skills in public health politics.